1987
DOI: 10.1113/jphysiol.1987.sp016723
|View full text |Cite
|
Sign up to set email alerts
|

Electromyographic responses of a nasal muscle to stimulation of the nasal vestibule in the cat.

Abstract: SUMMARY1. The effects of nasal stimulation using an air jet or balloon on the electromyographic (e.m.g.) activity ofa nasal muscle, the levator labii superioris alaeque nasi component of the quadratus labii superioris muscle, were studied in the anaesthetized cat.2. Respiratory related nasal e.m.g. activity was recorded and this normally consisted of two components, one coinciding with the onset of inspiratory airflow and a larger component which commenced at the onset of expiratory airflow and often persisted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…It was previously suggested that the nose is rich with mechano-and thermoreceptors, but very little is known about their structure, location, and function (53). Previous experiments suggested that receptors of the nasal trigeminal nerve sense flow, pressure, and temperature in cats and rats (54,55); however, in humans they were shown to play no part in airflow sensation (56). Integrins or primary cilia on the NECs surface may also function as mechanoreceptors.…”
Section: Nasal Sensation and Clinical Aspects Of Mechanophysical Stimulationsmentioning
confidence: 99%
“…It was previously suggested that the nose is rich with mechano-and thermoreceptors, but very little is known about their structure, location, and function (53). Previous experiments suggested that receptors of the nasal trigeminal nerve sense flow, pressure, and temperature in cats and rats (54,55); however, in humans they were shown to play no part in airflow sensation (56). Integrins or primary cilia on the NECs surface may also function as mechanoreceptors.…”
Section: Nasal Sensation and Clinical Aspects Of Mechanophysical Stimulationsmentioning
confidence: 99%